Enzyme Treatment-Free and Ligation-Independent Cloning Using Caged Primers in Polymerase Chain Reactions - Akinori Kuzuya; Keita Tanaka; Hitoshi Katada; Makoto Komiyama (Molecules, 2011)
A new simple scheme for constructing recombinant vectors that does not require any restriction enzyme, ligase, or any other special enzyme treatment has been developed. By using caged primers in PCR, unnatural sticky-ends of any sequence, which are sufficiently long for ligation-independent cloning (LIC), are directly prepared on the product after a brief UVA irradiation. Target genes and vectors amplified by this light-assisted cohesive-ending (LACE) PCR join together in the desired arrangement in a simple mixture of them, tightly enough to be repaired and ligated in competent cells.